SOCIAL CAPITAL AND SYMBOLIC CAPITAL: ANALYSIS THE INFLUENCE OF INTERACTIONS AMONG CAPITALS ON THE BEHAVIOR OF THE CHARACTERS ANA AND WILLIAM IN THE MOVIE UPGRADED (2024) - Aqila Firda Zahro; Adiva Alzahra Alwi; Haura Khansa; Ramadita Putri Ananta; Sabrina Fidhi Ramadhani; Pingkan Ary Ana; Rina Saraswati, M.Hum.; Kukuh Yudha Karnanta, M.A. (Cahaya Ilmu Bangsa Institute, 2024)
Upgraded (2024), directed by Carlson Young, tells a romance story about the competitive world of work with the protagonist Ana, a young woman who is struggling to establish herself in an art world which is full of expectations and high competition. This article aims to explore the influence of interactions among social capital and symbolic capital on the behavior of the main characters Ana and William in the movie Upgraded (2024). This analysis highlights the complexities of social mobility and the transformative power of agency, illustrating how personal capital can impact one’s position in the competitive world. Ultimately, Upgraded (2024) offers a nuanced exploration of how these forms of capital interact to influence behavior. The characters' journeys reveal that the successful navigation of both capitals is essential to achieving fulfillment in their respective lives. Thus, understanding this dynamic not only enriches our interpretation of the film but also highlights the broader social implications of identity construction and relational dynamics in contemporary culture.